2020
DOI: 10.1186/s12875-020-01186-x
|View full text |Cite
|
Sign up to set email alerts
|

Minor surgery in general practice in Ireland- a report of workload and safety

Abstract: Background: The provision of minor surgical services is an established part of the task profile of general practitioners (GPs) in many countries in Europe and elsewhere. This study aimed to collect data on the clinical process and outcomes for specified minor surgical procedures undertaken in Irish general practice by GPs experienced in minor surgery in order to document the scope and safety of minor surgery being undertaken. Methods: Over a six-month period, 24 GPs in 20 practices recorded data on a predeterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Is it safe, and will it reduce national health costs ? 1,[5][6][7][9][10][11]14,18,20,21,23,27,29 Nelligan et al demonstrated that OBMS driven entirely by family physicians significantly lowered health spending at their AMC. Perhaps more equitable payment for OBMS (greater than 20% of hospital rates) could still contribute to lower national health care costs, and also better support the GP practices to provide the proper equipment and staffing to provide OBMS in safe and timely manner.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Is it safe, and will it reduce national health costs ? 1,[5][6][7][9][10][11]14,18,20,21,23,27,29 Nelligan et al demonstrated that OBMS driven entirely by family physicians significantly lowered health spending at their AMC. Perhaps more equitable payment for OBMS (greater than 20% of hospital rates) could still contribute to lower national health care costs, and also better support the GP practices to provide the proper equipment and staffing to provide OBMS in safe and timely manner.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Office-based minor surgery (OBMS) has traditionally been a feature of general practice. [1][2][3][4][5][6][7][8][9][10][11] OBMS refers to all surgical procedures performed under local anesthetic, typically in the office setting. This includes a wide variety of procedures, ranging from minor excisions of dermatological imperfections and tumors, incision of abscesses, suturing wounds, and removing foreign objects, to more therapeutic procedures such as elective partial matrixectomy and thrombosed hemorrhoid treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a trend in general practice towards evolving services provided and utilising the skills in primary care. This would in turn augment and support the care provided by secondary care [4]. Currently, many minor procedures, such as punch biopsies and basic non-melanoma skin surgeries, are carried out in a fully staffed surgical theatre, increasing the burden on secondary care physicians.…”
Section: Introductionmentioning
confidence: 99%